Determinants of Nepal's Bilateral Trade in the SAARC Region: A Gravity Model Approach using PPML Estimator - Bhattarai, Sujan; Subedi, Sandu (Quest Journal of Management and Social Sciences, 2025)
Background: International trade is crucial for economic growth, particularly for landlocked developing countries like Nepal. Despite regional trade agreements like SAFTA, Nepal faces a persistent trade deficit within the SAARC region, obstructed by structural constraints and political tensions. Purpose: Using a gravity model, this study will analyse the determinants of Nepal's bilateral trade and exports with SAARC countries. It sought to assess the effectiveness of regional integration efforts for Nepal and identify key economic and policy factors shaping its trade performance. Methods: A panel dataset for seven SAARC countries (2009-2022) was analysed using the Poisson Pseudo-Maximum Likelihood (PPML) estimator. Models for total trade and exports incorporated traditional gravity variables (GDP, distance), socio-economic factors (exchange rates, tariffs, economic freedom), policy-related dummies (common border, BIMSTEC, India blockade, COVID-19), and an interaction term between tariffs and economic freedom. Findings: This research reveals that economic size and geographic distance significantly affect trade flows. Similarly, Partner country GDP and common borders positively influenced trade. Further, Nepal's exchange rate depreciation has negatively affected trade. The effect of several dummy variables on total trade flow and exports is diverse, such as the economic blockade by India, which has shown significant negative effects on exports. While COVID-19 negatively impacted total trade, it positively influenced exports. Higher economic freedom was found to reduce the adverse impact of tariffs on both total trade and exports. Conclusion: While Nepal's landlocked geography poses trade barriers, strong institutions help mitigate these constraints. Shifts in GDP-trade patterns reflect evolving export potential, though currency depreciation remains challenging. Strengthening governance, trade infrastructure, and export diversification is essential for deeper regional integration. Keywords: International Trade, Export Performance, Gravity Model, PPML estimators, SAARC JEL Codes: F14, F15, F18